Maternal and Child Survival : Findings from Five Countries Experience in Addressing Maternal and Child Health Challenges - Cortez, Rafael; Saadat, Seemeen; Chowdhury, Sadia; Sarker, Intissar (World Bank, Washington, DC, 2014)
Considerable progress has been made towards the achievement of the Millennium Development Goals (MDGs) since 1990. Although advances in improving MDG 4 and MDG 5a (reducing child and maternal mortality, respectively) have been made, progress is some countries have been insufficient. While some countries have made substantial gains, others have not. This paper is part of a larger study that aims to address this gap in knowledge. The paper discusses the findings from qualitative case studies of five countries that are either on track to meet MDGs 4 and 5a by 2015 or have made significant progress to this end (Bolivia, China, Egypt, Malawi and Nepal). Although they have different socio-economic characteristics, all have made significant advancements due to a strong commitment to improving maternal and child health. To do this, strong political commitment, through policies backed by financial and programmatic support, was critical. In addition, focusing on the most vulnerable populations helped increase access to and use of services. Empowering women and families through education, employment, and poverty reduction programs have led to better health outcomes. These countries still face challenges, however, in terms of the evolving health system, and changes at the economic, social and political levels. Future qualitative and quantitative analyses on the returns of health investments, the political context and institutional arrangements at the country level could help deepen the understanding of the ways in which various countries, with their unique conditions, can improve MCH.